KEBIJAKAN KETAHANAN ENERGI BERBASIS ENERGI LISTRIK PADA BIDANG TRANSPORTASI GUNA MENDUKUNG PERTAHANAN NEGARA DI INDONESIA: SEBUAH KERANGKA KONSEPTUAL - Diska Resha Putra; Donny Yoesgiantoro; Suyono Thamrin (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2020)
Indonesia is still very dependent on the use of fossil energy. The use of fossil energy in Indonesia reaches 95% of Indonesia's energy needs. As much as 50% of fossil energy used in Indonesia comes from oil. The low increase in fossil energy, sustainable energy use, and the use of new and renewable energy are the main concerns of the Indonesian government. This shows the importance of energy security. As a form of energy security, the government has made a policy to use alternatives in the transportation sector that uses electric energy. Therefore, it aims to describe the conceptual framework framework of the electricity-based energy security policy in the transportation sector in Indonesia to support national defense. This writing uses a literature study approach. The findings from this are three concepts in energy security, namely: (1) the existence of a population of energy resources that is sufficient for energy demand, (2) the fulfillment of energy needs with the support of various facilities and other supporting parties such as distribution, transportation, production division and others. other, and (3) relating to the minimal negative impact of energy production and consumption on the surrounding environment as well as the health of humans and other creatures. Therefore, policies related to energy security, particularly in the transportation sector, are manifested in a statement of energy security. This form of energy security will have a positive impact on national resilience and of course can support national defense.